Study of the application of plasma sprayed coatings on the sections of the Astazou III B turbo - jet engine - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The plasma spray process is used extensively in the aerospace industry for manufacturing key components exposed to excessively high temperatures, aggressive chemical environments, wear, abrasion, erosion and cavitation. The process covers a large field of parameters so that almost every layer can be combined with any other as well as with the base material. Coatings can be deposited uniformly; therefore, they allow worn components to be brought to final dimensions in the process of aircraft repair. This research shows an effective procedure of the application of plasma spray coatings on the parts of the Astazou III B turbo - jet engine in the process of repair.The engine manufacturer,Turbomeca, has prescribed that powders should be deposited by plasma spray systems under designation Metco 3M and 7M for the prescribed parameters of powder deposition, so that during the application of other plasma spray depositing systems the parameters must be tested and optimized. The aim was to apply the Plasmadyne plasma spray system during the repair process and to optimize the parameters, which will enable producing coatings that fulfill all the criteria prescribed in the engine manufacturer standard. The optimization of the parameters was carried out with a plasma gun MINI - GUN II with a large number of samples. This paper presents the optimal parameters of the deposition on the ASTAZOU III B engine casing, casing frame, duct and oil tank.The assessment of the coating mechanical properties was done by the HV0.3 microhardness testing method. Tensile bond strength of the coatings was investigated by a tensile test. The microstructures of the coating layers were evaluated on an optical microscope - OM. The analysis of the microstructures and the mechanical characteristics of the coatings was done in accordance with the TURBOMECA standard. The quality of the deposited coatings was confirmed by a 42-hour test of the ASTAZUO III B engine parts on a test stand. The performed tests have confirmed the quality of the coatings thus enabling the application of the plasma spray technology in the process of the ASTAZOU III B engine overhaul.